ANALISIS PENGARUH PERILAKU HERDING INVESTOR ASING, VOLATILITAS INDEKS HARGA SAHAM GABUNGAN, TINGKAT INFLASI, DAN KAPITALISASI PASAR TERHADAP RETURN PASAR (Studi Kasus pada Pasar Saham Indonesia Periode Januari 2005-Desember 2014) - Demi Pangestuti, Irene Rini; Nida ‘Ul Chasanah, Fatihah (Faculty of Economics and Business Diponegoro University, 2015)
Market return is the difference of Composite Stock Market Index certain period and Composite Stock Market Index last period. The purpose of this study is to examine the variabels influencing market return in Indonesian Stock Market. TheÂ behavioural ofÂ foreign investors herding, market volatility, inflation rates, market capitalization are used as predictors of market return.This research using the method of Ordinary Least Square Regression (OLS Regression), is based on data net buy and net sell volume of foreign investors, Composite Stock Market Index daily, inflation rate, market capitalization and market return monthly for 2005-2014 period. The reason research using Indonesian Composite Stock Market Index is the market is one of emerging market in ASEAN with high growth intensity than other stock market in ASEAN. OLS Regression Method is applied to examine the effect of foreign investors herding, market volatility, inflation rate and market capitalization on market return.The results of OLS Regression analysis shows that partially market volatility have significant negative impact to market return and inflation rate have significant negative impact to market return, but foreign investors herding have no significant positive impact to market return and market capitalization have no significant positive impact to market return.